Asymmetric migration dynamics of the tropical Asian and Australasian floras - Li-Guo Zhang; Xiao-Qian Li; Wei-Tao Jin; Yu-Juan Liu; Yao Zhao; Jun Rong; Xiao-Guo Xiang (Plant Diversity, 2023)
The tropical Asian and Australasian floras have a close relationship, and is a vital distribution pattern of seed plants worldwide. As estimated, more than 81 families and 225 genera of seed plants distributed between tropical Asia and Australasia. However, the evolutionary dynamics of two floras were still vague. Here, a total of 29 plant lineages, represented the main clades of seed plants and different habits, were selected to investigate the biotic interchange between tropical Asia and Australasia by integrated dated phylogenies, biogeography, and ancestral state reconstructions. Our statistics indicated that 68 migrations have occurred between tropical Asia and Australasia since the middle Eocene except terminal migrations, and the migration events from tropical Asia to Australasia is more than 2 times of the reverse. Only 12 migrations occurred before 15 Ma, whereas the remaining 56 migrations occurred after 15 Ma. Maximal number of potential dispersal events (MDE) analysis also shows obvious asymmetry, with southward migration as the main feature, and indicates the climax of bi-directional migrations occurred after 15 Ma. We speculate that the formation of island chains after the Australian–Sundaland collision and climate changes have driven seed plant migrations since the middle Miocene. Furthermore, biotic dispersal and stable habitat may be crucial for floristic interchange between tropical Asia and Australasia.